Diverse plant-associated pleosporalean fungi from saline areas: ecological tolerance and nitrogen-status dependent effects on plant growth - Qin, Yuan; Pan, Xueyu; Kubicek, Christian; Druzhinina, Irina; Chenthamara, Komal; Labbé, Jessy L.; Yuan, Zhilin (Frontiers in Microbiology, 2017)
Similar to mycorrhizal mutualists, the rhizospheric and endophytic fungi are also considered to act as the active regulators of host fitness (e.g., nutrition and stress tolerance). Although considerable work has been done in some of these areas, it is still poorly understood whether a general array of plant-associated fungi occurs in habitats with extreme conditions and to what extent they contribute to improved plant performance. Here, we investigated the root and seed-associated fungi from six halophytes growing in saline areas of China, and found that pleosporalean taxa (Ascomycota) were most frequently isolated. A total of twenty-seven representative isolates were selected for construction of the phylogeny based on the multi-locus data (partial 18S rDNA, 28S rDNA, and transcription elongation factor 1-α), which classified them into seven families, one clade potentially representing a novel lineage. To find out whether these fungi are capable of adapting to unfavorable conditions, the effect of temperature, pH, ionic and osmotic stress on fungal growth was examined. The data revealed a wide pH tolerance, while most isolates showed a variable degree of sensitivity to increasing concentration of either salt or sorbitol. Subsequent plant-fungal co-culture assays indicated that most isolates had only neutral or even adverse effects on plant growth in the presence of inorganic nitrogen. Interestingly, however, when provided with organic nitrogen sources, the majority of the isolates could significantly improve plant growth, and particularly stimulated the aboveground biomass formation. Most of the fungi preferred organic nitrogen over its inorganic counterpart, thus suggesting that these fungi can readily utilize organic nitrogen and mineralize it inorganic nitrogen, which is easily accessible for plant uptake. Microscopic observation further revealed that several isolates can successfully colonize the roots and form melanized hyphae and/or microsclerotia-like structures in root cortical cells, supporting the evidence of assigning them as dark septate endophytes. This work provides a better understanding of the symbiotic relationship between plants and pleosporalean fungi, suggesting that great potential value of this fungal group can be utilized in organic agriculture production.